EFEKTIVITAS PENGGUNAAN AUGMENTED REALITY (AR) DALAM MENINGKATKAN ATENSI BIOLOGI SISWA - Asy Syifa Qalbi; Muhyiatul Fadilah; Heffi Alberida; Rahmadhani Fitri (Universitas Nias Raya, 2026)
The decline in student attention in biology learning is a serious challenge because it has an impact on low conceptual understanding and overall learning outcomes. This study aims to determine the effectiveness of using Augmented Reality (AR) in improving students' biological attention. The method used is the Systematic Literature Review (SLR) by analyzing 30 articles from the Google Scholar, ScienceDirect, DOAJ, and Taylor and Francis databases published between 2019–2024. The research instrument is in the form of article analysis guidelines, while the data collection technique is carried out through screening inclusion and exclusion criteria. Data were analyzed descriptively-qualitatively. The results of the study showed that the use of AR had a positive impact on increasing student attention both in terms of cognitive, behavioral, and emotional aspects. The conclusion of this study states that AR is an effective medium for improving attention in biology learning. It is recommended that the development of AR content continues to be improved and supported by adequate and sustainable teacher training.